2018
DOI: 10.1098/rsos.180041
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized shift of oral, faecal and urinary microbiotas in bats and natural infection dynamics during seasonal reproduction

Abstract: Seasonal reproduction is a period of extreme physiological and behavioural changes, yet we know little about how it may affect host microbial communities (i.e. microbiota) and pathogen transmission. Here, we investigated shifts of the bacterial microbiota in saliva, urine and faeces during the seasonal reproduction of bats in South Africa, and test for an interaction in shedding patterns of both bacterial (Leptospira) and viral (adeno- and herpesviruses) agents. Based on a comparative approach in two cave-dwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Previous studies testing the role of pathogens shaping microbial communities have used evidence of current infection (e.g. qPCR; Dietrich, Kearney, Seamark, Paweska, & Markotter, 2018;Zink et al, 2015) rather than previous exposure based on serological evidence. When we sampled the moose gut microbial communities, the animal may not be experiencing the infection, and this may be the reason we did not detect an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies testing the role of pathogens shaping microbial communities have used evidence of current infection (e.g. qPCR; Dietrich, Kearney, Seamark, Paweska, & Markotter, 2018;Zink et al, 2015) rather than previous exposure based on serological evidence. When we sampled the moose gut microbial communities, the animal may not be experiencing the infection, and this may be the reason we did not detect an effect.…”
Section: Discussionmentioning
confidence: 99%
“…Some species may interact more frequently within roosts than others, such as by using the same microhabitat or by overlapping within roosts during the same season; thus, there would be a greater potential for ectoparasite and microbial transmission. Fluctuations in colony size and bat community composition between summer maternity colonies and winter roosts would also be expected to influence parasite exchange (Dietrich et al, 2018). Our sampling approach did not capture these important variables and should be considered in future studies.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Across species, Webber et al [32] found that viral richness was positively correlated with group size as predicted by the contact-rate hypothesis. In turn, at the intra-specific level Dietrich et al [33] found an important seasonal shift in prevalence with a significant increase in AdVs shedding during reproduction while studying AdVs prevalence in two bats (Miniopterus natalensis and Rousettus aegyptiacus). The aim of this study is to advance our understanding of heterogeneity in the prevalence of AdVs in bats, testing the association between traits and presence of AdVs at both the among-species and within-species levels.…”
Section: Introductionmentioning
confidence: 99%